2023
DOI: 10.3390/jcm12030990
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MCM9 in the Etiology of Sertoli Cell-Only Syndrome and Premature Ovarian Insufficiency

Abstract: Infertility in couples is a common problem, with both female and male factors contributing to similar extents. Severe, congenital disorders affecting fertility are, however, rare. While folliculogenesis and spermatogenesis are generally orchestrated via different mechanisms, some genetic anomalies can impair both female and male gametogenesis. Minichromosome maintenance complex component 9 (MCM9) is involved in DNA repair and mutations of the MCM9 gene have been previously reported in females with premature ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Although the female Mcm9 knock-out mice were sterile due to a lack of oocytes, male knock-outs were fertile with fewer germ cells compared to their Wt counterparts [ 94 , 95 ]. By contrast, both male and female humans are infertile if the MCM9 gene is disrupted [ 30 , 96 ]. These studies highlight some of the limitations when using meiosis and DNA repair genes in mouse models when trying to recapitulate gonadal development processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the female Mcm9 knock-out mice were sterile due to a lack of oocytes, male knock-outs were fertile with fewer germ cells compared to their Wt counterparts [ 94 , 95 ]. By contrast, both male and female humans are infertile if the MCM9 gene is disrupted [ 30 , 96 ]. These studies highlight some of the limitations when using meiosis and DNA repair genes in mouse models when trying to recapitulate gonadal development processes.…”
Section: Discussionmentioning
confidence: 99%
“…An example of a well-established autosomal-recessive (AR) gene is FSHR , the first discovered POI locus 8 . Other examples of recessive POI genes with monoallelic findings by Ke et al are SPIDR 9,10 , MSH4 11 , EIF2B2 12 , and MCM9 13 . Conducted family-based studies have identified no POI phenotype in the heterozygous mothers (carriers of damaging variants) of affected homozygous daughters.…”
mentioning
confidence: 96%
“…The available data for 18 genes (in this commentary referred as 'Unclear') was insufficient to conclusively determine their specific inheritance mode. , and MCM9 13 . Conducted family-based studies have identified no POI phenotype in the heterozygous mothers (carriers of damaging variants) of affected homozygous daughters.…”
mentioning
confidence: 99%